The Effect of Symptom Duration on Outcomes After Fusion for Degenerative Spondylolisthesis. Issue 5 (August 2019) - Fleming, John; Glassman, Steven D.; Miller, Adam; Dimar, John R.; Djurasovic, Mladen; Carreon, Leah Y.
Study Design: Longitudinal comparative cohort. Objectives: To determine if the duration of symptoms in patients with degenerative spondylolisthesis affects postoperative outcomes after 1- or 2-level decompression and fusion. Methods: Patients undergoing primary surgery for grade 1 degenerative spondylolisthesis at a single Quality Outcomes Database (QOD) participating site were identified. Demographic, surgical and patient-reported outcomes (PROs) data, including baseline and 12-month postoperative Oswestry Disability Index (ODI), back pain (BP, 0-10), leg pain (LP, 0-10), and EuroQOL-5D (EQ-5D) scores were collected. Individual medical records were reviewed for data on duration of symptoms prior to surgery. Patients were stratified into 3 cohorts—those with preoperative symptom duration of less than 1 year, 1 to 2 years, or greater than 2 years. Results: Complete data was available in 123 patients. Significant improvement in ODI, BP, and LP scores were observed in all groups. At 12-month follow-up improvement in ODI, BP, or LP was similar among the cohorts; with a trend toward significance with better improvement in LP scores in patients with a symptom duration of less than 1 year to those with symptom duration greater than 2 years ( P = .058). Conclusions: The duration of symptoms up to 2 years prior to surgery may not be a useful predictor of improvement of back pain or disability scores in patients with spondylolisthesis requiring decompression and fusion. Although there was a positive trend for improvement in leg pain for those with a shorter duration of symptoms, this did not reach statistical significance in our study.